Shepherds of the empire : Germany's conservative Protestant leadership--1888-1919 - Correll, Mark R. (Fortress Press, 2014)
The late nineteenth century was a time of rapid industrialization, mass politicization, and modern philosophy. The resulting political and cultural upheaval confronted the German protestant church with deep questions of identity. On the one side sat an educated academic guild whose explorations of history, philology, and emerging social scientific disciplines gave rise to serious questions about the Christian faith and its meaning for today. On the other sat parish clergy faced with the complexities of daily life and leadership in common communities. For these parish clergy the pressure was great to support and bolster people not only in their life as Christians, but in their life as Germans. Shepherds of the Empire engages timeless questions of identity and faith through the time-bound work of four key thinkers who attempted, and ultimately failed, to carve a middle way for the German parish clergy in that environment.